The Percentage of [−2]Pro–Prostate-Specific Antigen and the Prostate Health Index Outperform Prostate-Specific Antigen and the Percentage of Free Prostate-Specific Antigen in the Detection of Clinically Significant Prostate Cancer and Can Be Used as Reflex Tests - Garrido, MM (2022)
Context.—: There is a need to avoid the overdiagnosis of prostate cancer (PCa) and to find more specific biomarkers. Objective.—: To evaluate the clinical utility of [-2]pro-prostate-specific antigen ([-2]proPSA) derivatives in detecting clinically significant PCa (csPCa) and to compare it with prostate-specific antigen (PSA) and with the percentage of free PSA (%fPSA). Design.—: Two hundred thirty-seven men (PSA: 2-10 ng/mL) scheduled for a prostate biopsy were enrolled. Parametric and nonparametric tests, receiver operating characteristic curves, and logistic regression analysis were applied. Outcomes were csPCa and overall PCa. Results.—: Both [-2]proPSA derivatives were significantly higher in csPCa and overall PCa (P < .001). The areas under the curves for the prediction of csPCa were higher for the percentage of [-2]proPSA (%[-2]proPSA) (0.781) and the prostate health index (PHI) (0.814) than for PSA (0.651) and %fPSA (0.724). There was a gain of 11% in diagnostic accuracy when %[-2]proPSA or PHI were added to a base model with PSA and %fPSA. Twenty-five percent to 29% of biopsies could have been spared with %[-2]proPSA (cutoff: ≥1.25%) and PHI (cutoff: ≥27), missing 10% of csPCas. The same results could have been achieved by using [-2]proPSA as a reflex test, when %fPSA was 25% or less (cutoffs: ≥1.12% and ≥24 for %[-2]proPSA and PHI, respectively). Conclusions.—: The [-2]proPSA derivatives improve the diagnostic accuracy of csPCa when the PSA value is between 2 and 10 ng/mL, sparing unnecessary biopsies and selecting patients for active surveillance. [-2]proPSA can be used as a reflex test when %fPSA is 25% or less, without reducing the diagnostic accuracy for csPCa and the number of spared biopsies.